Hydrophilic polymer embolization following flow diversion of cerebral aneurysms. Issue 4 (August 2021) - Abdalkader, Mohamad; Sathya, Anvitha; Ma, Alice; Cervantes-Arslanian, Anna M; Chung, David Y; Barest, Glenn; Nguyen, Thanh N
Foreign body embolization is a rare and potentially under-recognized complication of neuroendovascular procedures. This complication should be considered in the differential diagnosis for clinical or radiological deterioration following neurovascular interventions. We report a case of foreign body hydrophilic coating embolization that occurred following an attempted flow diversion of an intracranial aneurysm with dramatic flare-up after repeat exposure. We also provide a literature review of all reported cases of hydrophilic polymer embolization following flow diversion procedures.